Cognitive Behavior Therapy (CBT) Pada Pasien Pasca Stroke dengan Depresi Literatur Review - Santi Rinjani; Suryani Suryani; Aat Sriati; Andri Nugraha (Jurnal Medika Cendikia, 2021)
Stroke is one of the most serious diseases because of the death and mortality rate. The World Health Organization (WHO) revealed that stroke is the second leading cause of death in the world, killing 6.2 million people. Half of all have problems returning to their pre-stroke state in their daily routine. Especially the psychosocial problems of stroke survivors have a negative impact on their quality of life, causing depression. The level of anxiety and depression can be reduced by means of the patient being given therapy, namely Cognitive Behavior Therapy. This literature search aims to analyze the results of research that focuses on the effect of Cognitive Behavioral Therapy on helplessness, depression in stroke patients. Method This study was conducted by reviewing the literature through electronic media on Sience Direct and Google Scholar and using the keywords "cognitive behavioral therapy in stroke patients and depression", after obtaining 6 articles that met the criteria with a maximum publication year of the last 10 years. The results showed that cognitive behavioral therapy is a type of short-term behavioral treatment that focuses on the patient considering the relationship between beliefs, thoughts, and feelings and following behavioral patterns and behaviors. During cognitive behavioral therapy, depression levels decreased and quality of life improved, psychosocial symptoms decreased, and self-efficacy expectations increased. There are three phases of cognitive behavioral therapy, namely the phase of behavior modification, cognitive restructuring, and reducing adverse effects. The conclusions of this study indicate that Cognitive Behavioral Therapy significantly reduces psychosocial problems, improves patients' quality of life and reduces depression.